2008
DOI: 10.1074/jbc.m802121200
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Phosphorylation and Phosphorylation-null Mutants on the Activity and Deamination Specificity of Activation-induced Cytidine Deaminase

Abstract: Activation-induced cytidine deaminase (AID) initiates somatic hypermutation and class switch recombination in B cells by deaminating C 3 U on transcribed DNA. Here we analyze the role of phosphorylation and phosphorylation-null mutants on the biochemical behavior of AID, including enzyme specific activity, processivity, deamination spectra, deamination motif specificity, and transcription-dependent deamination in the presence and absence of RPA. We show that a small fraction of recombinant human AID expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 44 publications
5
62
0
Order By: Relevance
“…We have found that AID expressed in Sf 9 insect cells can be phosphorylated on Ser 38 and Thr27 as well as two additional phosphorylation sites, Ser41 and Ser43 (Pham et al 2008). Analysis of this mass spectrometry data suggests that only one residue can be phosphorylated on AID at a time (Pham et al 2008).…”
Section: Aid Processive Deamination During Transcription Does Not Reqmentioning
confidence: 91%
See 4 more Smart Citations
“…We have found that AID expressed in Sf 9 insect cells can be phosphorylated on Ser 38 and Thr27 as well as two additional phosphorylation sites, Ser41 and Ser43 (Pham et al 2008). Analysis of this mass spectrometry data suggests that only one residue can be phosphorylated on AID at a time (Pham et al 2008).…”
Section: Aid Processive Deamination During Transcription Does Not Reqmentioning
confidence: 91%
“…This suggests that the jumping motion of APOBEC3G contributes to a significant portion of the processivity (Chelico et al 2006(Chelico et al , 2008. Deamination spectra of AID show large gaps between clustered deamination sites suggesting that the enzyme can jump and slide (Pham et al 2003(Pham et al , 2008Bransteitter et al 2004). Sliding seems to permit deamination of closely spaced residues whereas jumping would facilitate reaching multiple regions of an ssDNA substrate (figure 2c).…”
Section: (D) Contributions Of Sliding and Jumpingmentioning
confidence: 99%
See 3 more Smart Citations